Holocene climatic and human influences on lakes of the Yucatan Peninsula, Mexico: An interdisciplinary, palaeolimnological approach - Whitmore, T. J.; Brenner, M.; Curtis, J. H.; Dahlin, B. H.; Leyden, B. W. (Holocene, 1996)
We used palaeolimnological techniques to examine effects of Holocene climate change and human influence on lakes of the Yucatan Peninsula, Mexico. The three study lakes are located along a west-east transect that represents a gradient of increasing modern precipitation and density of former Maya settlement. At Lake Coba, an 880-cm sediment core yields a complete record of lacustrine sedimentation that began when the lake first filled similar to 8000 BP as groundwater level rose in response to rising sea level and increased precipitation. Diatom, ostracod, and delta(18)O evidence indicate that Lake Coba was initially shallow and saline. Coba, presently in the region of greatest rainfall, showed more episodic water-level changes than Lake San Jose Chulchaca or Lake Sayaucil. High lake level and fresh water were evident at 440 cm (similar to 2600 BP), followed by a decline in water levels and an increase in total ionic salinity to the present time. In a 613-cm core from Sayaucil, in the intermediate precipitation zone, total salinity was high between 600 and 400 cm (similar to 3050 and 2000 BP), followed by consistently higher water levels. Salinity was high in the lower portion of a 110-cm San Jose Chulchaca core (beginning similar to 1860 BP), followed by a gradual and consistent freshening of water to the present time.Trophic state changes and human influence on lakes were evaluated using diatom, delta(18)O, total P, sedimentary organic matter, and preliminary pollen data. Maximal human disturbance at Lake Coba, a densely settled Maya urban site, occurred during a deep-water event at 440 cm, followed by a decline in human influence and trophic state to the present time. Trophic state and linear sedimentation rates in Sayaucil increased significantly above 400 cm (after similar to 2000 BP), probably associated with initial Maya settlement near Xtojil and subsequent small-scale farming. Limnological disturbance may have preceded the period of maximal human occupation because initial land clearance and consequent soil erosion probably affected water quality substantially. San Jose Chulchaca lacks archaeological evidence of human occupation in the drainage, and shows gradual changes in trophic state not caused by human disturbance. With the exception of a C-14 date on wood from the base of the Coba core, C-14 dates and chronologies may be artificially old as a consequence of hard-water-lake error. Trophic state changes in the study lakes were generally consistent with known patterns of human settlement and population change. Late-Holocene water-level fluctuations were most pronounced in Lake Coba in eastern Yucatan, where modern rainfall is currently greatest, but lake level is generally lower than during much of the past. Lake level was relatively constant in Sayaucil in the central peninsula, whereas lake level in San Jose Chulchaca in the arid western portion of the peninsula increased gradually over time.
Vh189Times Cited:56Cited References Count:65